TNFSF15 facilitates human umbilical cord blood haematopoietic stem cell expansion by activating Notch signal pathway. Issue 19 (10th September 2020) - Ding, Yahui; Gao, Shan; Shen, Jian; Bai, Tairan; Yang, Ming; Xu, Shiqi; Gao, Yingdai; Zhang, Zhisong; Li, Luyuan
Abstract: The lack of efficient ex vivo expansion methods restricts clinical use of haematopoietic stem cells (HSC) for the treatment of haematological malignancies and degenerative diseases. Umbilical cord blood (UCB) serves as an alternative haematopoietic stem cell source. However, currently what limits the use of UCB‐derived HSC is the very low numbers of haematopoietic stem and progenitor cells available for transplantation in a single umbilical cord blood unit. Here, we report that TNFSF15, a member of the tumour necrosis factor superfamily, promotes the expansion of human umbilical cord blood (UCB)‐derived HSC. TNFSF15‐treated UCB‐HSC is capable of bone marrow engraftment as demonstrated with NOD/SCID or NOD/Shi‐SCID/IL2Rgnull (NOG) mice in both primary and secondary transplantation. The frequency of repopulating cells occurring in the injected tibiae is markedly higher than that in vehicle‐treated group. Additionally, signal proteins of the Notch pathway are highly up‐regulated in TNFSF15‐treated UCB‐HSC. These findings indicate that TNFSF15 is useful for in vitro expansion of UCB‐HSC for clinical applications. Furthermore, TNFSF15 may be a hopeful selection for further UCB‐HSC application or study.